A century of chasing the ice: delayed colonisation of ice‐free sites by ground beetles along glacier forelands in the Alps. Issue 1 (16th July 2013) - Brambilla, Mattia; Gobbi, Mauro
<x xml:space="preserve">Abstract</x> Climate change is affecting species distribution, composition of biological communities, and species traits. Despite the growing body of knowledge on the reaction of species to climate change, the potentially delayed response of species is still severely understudied. In this paper we modelled the time needed by ground‐living invertebrates to effectively react to habitat modification induced by climate change in relation to dispersal abilities. We analyzed the occurrence pattern of alpine ground beetles (carabids) along areas recently freed by retreating glaciers in the central‐eastern Italian Alps, to test how the synergic effects of time since deglaciation and environmental factors may affect the colonisation process. Different times of response to climate change in ground beetles were found. Sites already hosting the land cover type suitable for our study taxon, but ice‐free for less than 100 yr, are mainly colonised by winged carabid beetles (which have high dispersal abilities and are mostly habitat generalists). No, or very few, wingless species (slow colonizers and ecologically specialized) occur within those sites. The overall pattern suggests that within a site, suitable land cover is established prior to colonization, due to a strong joint effect of time since deglaciation and land cover type. Long‐lasting habitat development at the fine scale is likely to result in a lack of specific resources (e.g. food items, or microhabitat), which is likely to contribute to delayed colonisation, which potentially could be tied also to dispersal abilities. Whatever the reason, the existence of a time‐lag often equal to or greater than 100 yr in species colonisation implies caution in predicting species' occurrence shifts following climate change.